Report on the 16th National Scientific Conference in the “Humanistic Ecology” Series: “Man for the City – the City for Man” (Warsaw, 26 October 2022) - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2022)
The report summarizes the 16th National Scientific Conference in the “Humanistic Ecology” series titled “Man for the City – the City for Man”, held on October 26, 2022, in Warsaw. Organized by the Department of Ecophilosophy at Cardinal Stefan Wyszyński University, the event brought together scholars, public officials, and NGO representatives to address the challenges of sustainable urban development. The interdisciplinary and hybrid-format conference featured 16 papers and 4 posters, focusing on urban ecology, climate resilience, and quality of life in cities. Selected contributions were published in the journal Studia Ecologiae et Bioethicae.